Conjugated Ladder Polymers: Unique Organic π-Conjugated Materials for Optoelectronics, Transistors, and Energy Harvesting and Storage - Kok Chan Chong; Teck Lip Dexter Tam; Ran Tao; Kang Le Osmund Chin; Ming Hui Chua; Jianwei Xu (Energy Material Advances)
Conjugated ladder polymers (cLPs) are polymers consisting of continuous fused aromatic rings with π conjugation along their backbone. This unique structure imparts cLPs with exceptional thermal, mechanical, and electrochemical stability, as well as notable optical and electrical properties due to their rigid, planar structures. Since the seminal work on the synthesis of high-molecular-weight, solution-processable poly(benzimidazobenzophenanthrolinedione) in 1969 by F. E. Arnold and R. L. Van Deusen, many cLPs have been developed for a variety of applications. This review focuses on both the synthesis and applications of cLPs for energy harvesting and storage devices, organic optoelectronics, and organic transistors. The former includes several facile synthetic methods, postsynthetic treatments, various characterization, and postprocessing of cLPs, focusing on film fabrication. The latter focuses on numerous applications, including organic thermoelectrics for energy harvesting, battery electrodes and organic supercapacitors for energy storage, and organic optoelectronics, including organic light-emitting diodes, organic photovoltaics, organic electrochromics, and organic photodetectors. It also covers organic transistors like organic field-effect transistors and organic electrochemical transistors. The review concludes with potential challenges and outlooks on cLPs in many organic electronics areas, offering a comprehensive perspective on their future development and potential.